Morphological, Crystallinity, and Functional Group Analysis of Coconut Shell-Based Activated Carbon with Carbonization Temperature Variations for Supercapacitor Electrode Potential - Anggita, Sheilla Rully; Prahesti, Arinda Yukashima Putri; Azizah, Tasya Salsabila; Arsini, Arsini (Diponegoro University Semarang Indonesia, 2025)
Supercapacitors are advanced energy storage devices with high power density and rapid charge–discharge capabilities. This study explores the potential of coconut shell–based activated carbon as an electrode material for supercapacitors. Coconut shell carbon powder was carbonized at temperatures ranging from 400°C to 700°C and chemically activated using 3M KOH for 24 hours. The activated carbon was then filtered, rinsed with distilled water until neutral pH, and dried at 120°C for 4 hours. Characterization was performed using Scanning Electron Microscopy (SEM), Brunauer–Emmett–Teller (BET) analysis, X-ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR). SEM images confirmed the formation of uniformly distributed pores, with higher carbonization temperatures leading to increased pore development. BET analysis showed that both surface area and pore volume increased with rising carbonization temperatures. XRD patterns revealed amorphous graphite-like carbon structures, with improved crystallinity at higher temperatures. FTIR spectra confirmed the presence of aromatic C=C and C–O functional groups. These results demonstrate that activated carbon derived from coconut shells exhibits favorable physicochemical properties, indicating strong potential as a low-cost and sustainable electrode material for supercapacitor applications.